Evaluating β-amyloidosis progression in Alzheimer’s disease with Mueller polarimetry - Borovkova, Mariia (Biomed Opt Express, 2020)
We applied the wide-field Mueller imaging polarimetry for the screening of formalin-fixed paraffin-embedded samples of mouse brain tissue at different stages of brain β-amyloidosis in Alzheimer’s disease (AD). The accumulation of amyloid-beta (Aβ) deposits throughout the brain tissue is one of the key pathological hallmarks observed with the AD progression. We demonstrate that the presence of Aβ plaques influences the properties of backscattered polarized light, in particular, its degree of depolarization. By means of statistical analysis, we demonstrate that the high-order statistical moments of depolarization distributions, acquired with the multi-spectral Mueller imaging polarimetry, can be used as sensitive markers of the growing presence of Aβ plaques. The introduced label-free polarimetric approach has a potential to facilitate the current practice of the histopathology screening in terms of diagnosis accuracy, time and cost efficiency.